A Hybrid MCDM Framework for Overcoming Barriers in the Covid-19 Vaccine Supply Chain - Ghorbani, Shahryar; Yıldırım, Figen; Bicer, Ali Altug; Zavadskas, Edmundas Kazimieras; Antucheviciene, Jurgita; Rostamzadeh, Reza (Transformations In Business & Economics, 2026)
The COVID-19 pandemic has posed unprecedented challenges globally, with the vac-cine supply chain (VSC) serving as a critical lifeline to mitigate the spread of the virus. This paper addresses the significant barriers to the COVID-19 VSC, identifies strategies for overcoming these barriers, and proposes a hybrid multi-criteria decision-making (MCDM) approach for prioritising these strategies. Using the Best-Worst Method (BWM) to determine the weights of barriers and the Weighted Aggregate Sum Product Assessment (WASPAS) method to rank strategies, this study reveals that the most significant barriers include challenges in monitoring and controlling vaccine temperature, maintaining cold chain logistics, and dealing with costs and suboptimal immunisation budgets. The findings suggest that fostering collab-oration, cooperation, and coordination across organisations is the most effective strategy for overcoming the mentioned barriers. This research provides actionable insights for policymakers, healthcare systems, and vac-cine distributors to enhance the efficiency and resilience of the COVID-19 VSC, contributing to global vaccination efforts. The study’s implications extend to future pan-demic response planning, offering strategies to build more sustainable and adapt-able vaccine supply chains.